Spiegelmer inhibition of MCP-1/CCR2: potential as an adjunct immunosuppressive therapy in transplantation - Kalnins, Aivars; Andrassy, Martin; Bazhin, Alexandr V.; Werner, Jens; Andrassy, Joachim (Scandinavian journal of immunology, 2015)
The rejection process remains the key unsolved issue after transplantation of disparate tissue. The CC chemokine monocyte chemoattractant protein-1 (MCP-1/CCL2) has been reported to be involved in the process of alloimmune interaction. Spiegelmers are l-oligonucleotides that can be designed to bind to pharmacologically relevant target molecules. Here, we tested a high-affinity Spiegelmer-based MCP-1 inhibitor (mNOX-E36) in an allogeneic heart transplant model. Fully vascularized allogeneic heterotopic heart transplantations from BALB/c to C57BL/6 mice were performed. Mice were either treated with the anti-MCP-1-Spiegelmer (mNOX-E36) in monotherapy or in combination with subtherapeutic doses of cyclosporine A (CsA) (10 mg/kgBW/day) for 10 days. Controls received equivalent doses of a non-functional Spiegelmer (revmNOX-E36). Graft survival of allogeneic heart transplants was slightly but significantly prolonged under mNOX-E36 monotherapy (median graft survival 10 day ± 0.7) compared to revmNOX-E36 (median graft survival 7 day ± 0.3; P = 0.001). A synergistic beneficial effect could be seen when mNOX-E36 was administered in combination with subtherapeutic doses of CsA (18 day ± 2.8 versus 7 day ± 0.3; P < 0.0001). Levels of inflammatory cytokines and ‘alarmins’ were significantly reduced, and the number of F4/80+ cells was lower under combination therapy (1.8% ± 1.3%; versus 14.6% ± 4.4%; P = 0.0002). This novel inhibitor of the MCP-1/CCR2 axis (mNOX-E36), which has already proven efficacy and tolerability in early clinical trials, alleviates acute rejection processes in allogeneic transplantation especially when combined with subtherapeutic doses of CsA. Thus, mNOX-E36 may have potential as an adjunct immunomodulatory agent.